Categorization of Emotional Faces in Insomnia Disorder - Xu, Song; Liu, Xueping; Zhao, Lun (Frontiers in Neurology, 2020)
It has been proved that emotionally positive facial expressions are categorized much faster than emotionally negative facial expressions, the positive classification advantage (PCA). In the present study we investigated the PCA in primary insomnia patients. In comparison with controls, insomnia patients categorized emotional faces more slowly but there was no significant reduction in accuracy. In normal controls, happy faces were categorized faster than sad faces (i.e., PCA), which disappeared in inverted condition. Insomnia patients did not show evident PCA excepted for the overall delayed response for inverted than upright conditions. These data suggest the dysfunction of categorization of emotional faces in insomnia patients.